LOCAL WISDOM SAGO PLANTATIONS' ASSISTANCE IN SUSTAINABLE SAGO FARMING: INNOVATION CLUSTERS AS A SUSTAINABLE SAGO DEVELOPMENT MODEL (2000-2023) - Lili Dahliani (Fakultas Pertanian, Universitas Gunung Rinjani, 2023)
Global climate change poses a threat to food supplies since it leads to long-term droughts, excessive rains, pest infestations, and disease outbreaks. Indonesia has access to Sago, a promising food resource for ensuring food security. Sago thrives in wetlands and peatlands despite its considerable starch content. Therefore, effective sago plantation management requires addressing environmental, economic, social, and institutional considerations, as well as making significant advancements in sago innovation clusters. The presence of alternatives, such as the Sago innovation cluster, enhances collaboration and competitiveness. This study examines the growth of sago plantations and the indigenous knowledge systems used to maintain them. A qualitative systematic literature review (SLR) employing the TERASI technique scrutinizes pertinent journal articles published between 2000 and 2023. Harzing Publish, or Perish, utilizes Google Scholar as its primary source for academic literature. Retrieve scholarly material pertaining to the topics of